2002
DOI: 10.1523/jneurosci.22-01-j0001.2002
|View full text |Cite
|
Sign up to set email alerts
|

M5 Muscarinic Receptors Are Required for Prolonged Accumbal Dopamine Release after Electrical Stimulation of the Pons in Mice

Abstract: Midbrain dopamine neurons are activated directly by cholinergic agonists or by stimulation of the cholinergic neurons in the laterodorsal tegmental nucleus (LDT) of the pons in rats. In urethane-anesthetized mice, electrical stimulation of the LDT resulted in a rapid, stimulus-time-locked increase in dopamine release in the nucleus accumbens (NAc), followed several minutes later by a prolonged increase in dopamine release. In mutant mice with truncated M5 receptors, the prolonged phase of dopamine release was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
135
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 28 publications
14
135
0
Order By: Relevance
“…ACh infusions into the VTA potentiate ICSS (Redgrave and Horrell, 1976) and the ACh agonist carbachol and the AChE inhibitor neostigmine (which increases ACh concentrations) are both self-administered into the VTA (Ikemoto and Wise, 2002). M 5 receptor-deficient (M 5 À/À ) rats lack sustained NAc DA release following electrical stimulation of VTA cholinergic input (Forster et al, 2002), and striatal DA release induced by oxotremorine is significantly reduced in these M 5 receptor-knockout mice (Zhang et al, 2002). The absence of M 5 receptors on the VTA likely accounts for the lower rate of cocaine self-administration in M 5 À/À rodents (Fink-Jensen et al, 2003; Thomsen et al, 2005).…”
Section: Vta Acetylcholine and Rewardmentioning
confidence: 99%
“…ACh infusions into the VTA potentiate ICSS (Redgrave and Horrell, 1976) and the ACh agonist carbachol and the AChE inhibitor neostigmine (which increases ACh concentrations) are both self-administered into the VTA (Ikemoto and Wise, 2002). M 5 receptor-deficient (M 5 À/À ) rats lack sustained NAc DA release following electrical stimulation of VTA cholinergic input (Forster et al, 2002), and striatal DA release induced by oxotremorine is significantly reduced in these M 5 receptor-knockout mice (Zhang et al, 2002). The absence of M 5 receptors on the VTA likely accounts for the lower rate of cocaine self-administration in M 5 À/À rodents (Fink-Jensen et al, 2003; Thomsen et al, 2005).…”
Section: Vta Acetylcholine and Rewardmentioning
confidence: 99%
“…Antisense 14,15 and gene targeting technologies have emerged as powerful new tools in identifying the receptor subtypes involved in various muscarinic cholinergic functions. [16][17][18][19][20][21] Although pharmacological, neuroanatomical and clinical studies have suggested an important role of muscarinic receptors in synaptic plasticity and memory, the functions of the individual muscarinic receptor subtypes remain unclear. In this study, we have used M2 and M4 receptor single knockout (KO) as well as M2/M4 receptor double KO mice to investigate the functional importance of M2 and M4 receptors in the regulation of acetylcholine release in the hippocampus and in cognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have shown that activation of muscarinic receptors stimulates the activity of dopaminergic VTA neurons (18)(19)(20)(21). Given the known facilitatory effects of M 5 receptor activation on dopamine release from midbrain dopaminergic neurons (7,11), we hypothesized that M 5 receptor activation might modulate the behavioral and neurochemical correlates of drug reward and withdrawal. To test this hypothesis, we initially examined whether inactivation of the M 5 receptor gene affected the rewarding properties of morphine, the prototypical opiate analgesic, and the severity of morphine withdrawal symptoms.…”
mentioning
confidence: 99%
“…Consistent with this hypothesis, we recently demonstrated that muscarinic agonist-induced increases in striatal dopamine release were reduced in M 5 Ϫ/Ϫ mice (7). Moreover, Forster et al (11) recently reported that the sustained increase in dopamine levels in the nucleus accumbens (Acb) observed after electrical stimulation of the laterodorsal tegmental nucleus (12) is absent in M 5 Ϫ/Ϫ mice. Laterodorsal tegmental nucleus neurons represent the major source of cholinergic input to the dopamine-containing neurons of the VTA (13,14) that project to the Acb and other limbic areas (15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation